A Comparative Study on Various Spectrum Sharing Techniques. (2016) - Baby, Shilpa Merin; James, Manju
Abstract: As the numbers of wireless users are increasing, the scarcities of radio spectrum are also increasing. Spectrum sharing techniques are considered as one of the remedies to this situation. The efficiency of spectrum can be increased by this sharing process. A number of spectrum sharing techniques are available today. They have different features and they are evaluated under different factors. They differ in the mode of operation, interference management, and the situations where it has to be used. So a comparative study on various spectrum sharing techniques is very relevant. Different classification of spectrum sharing techniques and their comparison is done to obtain the basic idea about them.